Consequences of dark matter-dark energy interaction on cosmological parameters derived from SNIa data - Amendola, Luca; Campos, Gabriela C.; Rosenfeld, Rogerio (Arxiv, 2007)
Models where the dark matter component of the universe interacts with the dark energy field have been proposed as a solution to the cosmic coincidence problem, since in the attractor regime both dark energy and dark matter scale in the same way. In these models the mass of the cold dark matter particles is a function of the dark energy field responsible for the present acceleration of the universe, and different scenarios can be parameterized by how the mass of the cold dark matter particles evolves with time. In this article we study the impact of a constant coupling $δ$ between dark energy and dark matter on the determination of a redshift dependent dark energy equation of state $w_{DE}(z)$ and on the dark matter density today from SNIa data. We derive an analytical expression for the luminosity distance in this case. In particular, we show that the presence of such a coupling increases the tension between the cosmic microwave background data from the analysis of the shift parameter in models with constant $w_{DE}$ and SNIa data for realistic values of the present dark matter density fraction. Thus, an independent measurement of the present dark matter density can place constraints on models with interacting dark energy.
Gesehen am 15.11.2017